Solvent effect on photostability of butyl methoxy di benzoyl methane formulated in solution and emulsion (2015)
ABSTRACT: Objective: The current study was undertaken to correlate the impact of some cosmetics solvents in the photostability of butyl methoxy dibenzoyl methane (BMDBM) into systems with an increasing order of complexity, from simple solutions to emulsions. Methods: Solutions and emulsions containing BMDBM in different solvents were prepared and evaluated using spectrophotometer or transmittance analyzer, respectively. Also, emulsions containing BMDBM in combination with octyl methoxycinnamate (OMC) in ratio 1:1 and 1: 2, and in the presence of octocrylene in the ratio 1:2:1 were prepared. The percentage of decay absorbance at 356 nm was measured before and after irradiation at 500 W/m2 Results: The absorbance decay of BMDBM in solution was higher in solvents such as mineral oil, isopropyl palmitate and isopropyl myristate. Also, it was observed that concentration and degassing had an effect on the decay kinetics. In emulsions containing only, BMDBM, the absorbance decay did not exceed 20% in all solvents, suggesting a protective effect of the matrix. In the contrary, a decay of 90% was observed in emulsion containing BMDBM and OMC in a 1:2 ratio. When Oct was added to that emulsion, stabilization on the absorbance decay of BMDBM was detected. at intervals of 20 min until completing 100 min. Finally, a photolysis assay was carried to analyze deoxygenated and not BMDBM solutions. Conclusion: This study evidenced that the photochemistry of BMDBM is different in solutions and in emulsions. In solutions, the nature of solvents was important, while in emulsions the nature of UVB filters played a pivotal role in the stability of BMDBM.